Gene deletion as a possible strategy adopted by New World Leishmania infantum to maximize geographic dispersion. - Monique Florêncio; Marne Coimbra Batalha Chagas; Anderson Guimarães-Costa; Jullyanna Oliveira; Ingrid Waclawiak; Thamara K F Oliveira; Elvira Maria Saraiva; Anita Leocadio Freitas-Mesquita; José Roberto Meyer-Fernandes; Laura Aragão-Farias; Camilly Enes Trindade; Patricia Cuervo; et al. (PLoS Pathogens)
Background The present study investigates implications of a sub-chromosomal deletion in Leishmania infantum strains, the causative agent of American Visceral Leishmaniasis (AVL). Primarily found in New World strains, the deletion leads to the absence of the ecto-3'-nucleotidase/nuclease enzyme, impacting parasite virulence, pathogenicity, and drug susceptibility. The factors favoring prevalence and the widespread geographic distribution of these deleted mutant parasites (DEL) in the NW (NW) are discussed under the generated data. Methods We conducted phenotypic assessments of the sub-chromosomal deletion through in vitro assays with axenic parasites and experimental infections in both in vitro and in vivo models of vertebrate and invertebrate hosts using geographically diverse mutant field isolates. Results Despite reduced pathogenicity, the DEL strains efficiently infect vertebrate hosts and exhibit relevant differences, including enhanced metacyclogenesis and colonization rates in sand flies, potentially facilitating transmission. This combination may represent a more effective way to maintain and disperse the transmission cycle of DEL strains. Conclusions Phenotypic assessments reveal altered parasite fitness, with potential enhanced transmissibility at the population level. Reduced susceptibility of DEL strains to miltefosine, a key drug in VL treatment, further complicates control efforts. The study underscores the importance of typing parasite genomes for surveillance and control, advocating for the sub-chromosomal deletion as a molecular marker in AVL management.